Psychopharmacological Treatment and Psychological Interventions in Irritable Bowel Syndrome - Sinagra, Emanuele (Hindawi Publishing Corporation, 2012)
Irritable bowel syndrome (IBS) accounts for 25% of gastroenterology output practice, making it one of the most common disorders in this practice. Psychological and social factors may affect the development of this chronic disorder. Furthermore, psychiatric symptoms and psychiatric diseases are highly prevalent in this condition, but the approach to treating these is not always straightforward. As emphasized in the biopsychosocial model of IBS, with regard to the modulatory role of stress-related brain-gut interactions and association of the disease with psychological factors and emotional state, it proves useful to encourage psychopharmacological treatments and psychosocial therapies, both aiming at reducing stress perception. The aim of this paper is to analyze the effectiveness of psychopharmacological treatment and psychological interventions on irritable bowel syndrome.